1962
DOI: 10.1021/jm01240a011
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Activity of Newer Digitalis Glycosides and Aglycones

Abstract: In a ligroin-propylene glycol descending papergram, overnight development, the Rc for 16a-methyI-17a-hydroxyprogesterone (XVIb) is slightly greater than that of 16/3-methyl-l7 -hy droxyprogesterone (XVIa).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1977
1977
2004
2004

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 23 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…In cats, Bottcher, Lullrnann & Proppe (1973), using a heart-lung preparation, found that at 50% of peak inotropic effect, the relative potency of the bis-and mono-digitoxosides of digoxigenin were 1.26 and 1.44, compared with digoxin taken as unity. Marcus & others (1979, recalculated the data of Henderson & Chen (1962) and Chen (1 970) obtained in cats. On the basis of pmol mg-l body weight, the relative toxicities, compared with digoxin as unity, were digoxigenin-bis-digitoxoside 1.0, digoxigenin-mono-digitoxoside 1.4 and digoxigenin 0.3.…”
Section: Discussionmentioning
confidence: 99%
“…In cats, Bottcher, Lullrnann & Proppe (1973), using a heart-lung preparation, found that at 50% of peak inotropic effect, the relative potency of the bis-and mono-digitoxosides of digoxigenin were 1.26 and 1.44, compared with digoxin taken as unity. Marcus & others (1979, recalculated the data of Henderson & Chen (1962) and Chen (1 970) obtained in cats. On the basis of pmol mg-l body weight, the relative toxicities, compared with digoxin as unity, were digoxigenin-bis-digitoxoside 1.0, digoxigenin-mono-digitoxoside 1.4 and digoxigenin 0.3.…”
Section: Discussionmentioning
confidence: 99%